F32 Cognitive decline in huntington's disease (HD) in computerized arithmetic task. (September 2018) - Lunven, Marine; Hamet, Jennifer; Lemoine, Laurie; Youssov, Katia; Gabadinho, Alexis; Reilmann, Ralf; Busse, Monica; Craufurd, David; Rosser, Anne; Massart, Renaud; Bachoud-Lévi, Anne-Catherine
Abstract : Background: Designing tasks quickly assessed, sensitive enough to detect a decline in HD in a short amount of time in a small number of patients for assessing innovative therapies is a major challenge. We previously showed that HD patients are more impaired in subtraction than in multiplication (Teichmann et al., 2005). Here we assessed whether a digitalized version of the task may be useful in longitudinal follow-up. Aims: We explore the capacity of the arithmetic task to highlight cognitive decline in HD patients within a year. Methods: 34 HD patients (23 at stage I (HD1), 11 at stage II (HD2)) and 23 controls were included. They were tested on the computerized arithmetic task at baseline, month 1 (M1) and month 12 (M12) in three languages (French, English and German). The task consists in 20 multiplications and 20 subtractions with carry over displayed at random on the screen. Subjects were asked to indicate the correctness of the given solution. Response time (RT) and accuracy were recorded for each trial and statistical analysis were performed using linear mixed models. Results: HD patients were impaired in both subtraction and multiplication compared to controls at each time for RT (p<0.05). They increase the more time to solve subtraction than multiplication between M1 and M12 (p<0.05) but remains accurate (P>0.1). Post hoc analyses show that this decline was significant in HD2 patients (p<0.05) but not HD1. Conclusion: With the digitalized version of the tasks, we replicate that HD patients are impaired both in subtraction and multiplication. We showed that the task is sensitive to decline over one year, and more specifically the HD2 patients in the subtraction task. This suggests that this task should be implemented in future batteries, its psychometric properties are under analysis.